2008
DOI: 10.1100/tsw.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regional Pain Syndrome (CRPS/RSD) and Neuropathic Pain: Role of Intravenous Bisphosphonates as Analgesics

Abstract: Neuropathic pain is a sequela of dysfunction, injuries, or diseases of the peripheral and/or central nervous system pain pathways, which has historically been extremely difficult to treat. Complex regional pain syndrome (CRPS) types 1 and 2 are neuropathic pain conditions that have a long history in the medical literature but whose pathophysiology remains elusive and whose available treatment options remain few. While an exact animal model for CRPS doesn't yet exist, there are several animal models of neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…In several small randomized controlled trials, the use of bisphosponates has resulted in improvements in pain and function, suggesting a possible role in neuropathic pain [257,258]. In several small randomized controlled trials, the use of bisphosponates has resulted in improvements in pain and function, suggesting a possible role in neuropathic pain [257,258].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…In several small randomized controlled trials, the use of bisphosponates has resulted in improvements in pain and function, suggesting a possible role in neuropathic pain [257,258]. In several small randomized controlled trials, the use of bisphosponates has resulted in improvements in pain and function, suggesting a possible role in neuropathic pain [257,258].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…There are a variety of medications that have been used to treat the symptoms of CRPS with some success. These range from nonsteroidal anti‐inflammatory drugs (NSAIDs), steroids, and opioid analgesics and medications used to decrease nerve excitability such as anticonvulsants, tricyclic antidepressants, membrane‐stabilizing medications, the N‐methyl‐D‐aspartate (NMDA) receptor antagonist, ketamine , biophosphonates , and thalidomide . Salmon calcitonin for CRPS has been well studied ; however, one randomized controlled trial (RCT) found no more efficacy of the drug when compared with placebo .…”
Section: Treatment Options For Crpsmentioning
confidence: 99%
“…Der antinozizeptive Effekt der Bisphosphonate scheint aber nicht nur durch eine Hemmung der Osteoklastenaktivität und Osteoklastogenese zurückzuführen zu sein. Es gibt Hinweise, dass die Bisphosphonate auch die Aktivität der Neuropeptide-produzierenden Zellen hemmt (65).…”
Section: Medikamentöse Therapieunclassified